Eukaryotic parasites in feces of dogs collected in the streets of the urban zone of the coastal localities of Corral and Niebla in the south of Chile - Subiabre, Álvaro (2022)
The purpose of the study was to determine the prevalence of eukaryotic parasite eggs, larvae and cysts, as well as the number of helminth eggs or larvae per gram of dog faeces collected in the streets of the coastal towns of Niebla and Corral, in the south of Chile. The stool samples were processed by a combination of the qualitative methods of Modified Telemann and flotation with zinc sulphate solution, in addition to the quantitative method of Knight et al. (1972). The results showed that 85.1 and 92.3% of the samples were positive in Niebla and Corral, with no significant differences between localities. In both cities were identified eggs and larvae of Uncinaria stenocephala, Toxocara canis, Trichuris sp, Spirocerca sp, Capillariidae gen sp, and Taeniidae gen. sp, as well as oocysts of Cystoisospora canis and sporocysts of Sarcocystis sp, with the highest prevalence for U. stenocephala and Trichuris sp.